Forecasting the cost of diabetes: A systematic review - Viet, Nguyen Linh; Nhi, Tran Thi Yen; Nhi, Vo Ngoc Yen; Binh, Nguyen Thanh; Thuy, Nguyen Thi Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background: Diabetes poses a significant global health risk and is a leading cause of death and reduced life expectancy. Objective: A systematic review was conducted to collect studies predicting the economic burden of diabetes, offering insights for policymakers and stakeholders. Methods: A preferred reporting item for systematic reviews and meta-analyses (PRISMA)-guided systematic review identified relevant studies through a literature search in databases like Embase, PubMed, and Cochrane. Study quality was assessed using the Cost of Illness (COI) checklist. All costs were converted to 2024 US dollars after analyzing study characteristics and findings. Results: There were 16 of 1,667 studies from the three databases satisfied the selection and exclusion criteria. Studies were conducted in several nations across Asia, Europe, North America and globally with all studies were modeled using a descriptive cross-sectional design. Studies have projected the cost of diabetes over a period of 1–40 years. Incidence-based and prevalence-based methods were used in these studies. In previous studies, costs ranged from US0.19 billion to US3.1 trillion (USD 2024), depending on the region and forecast year. Incidence-based studies estimated total costs at US15.88 billion. When combining both approaches, the cost range was found to be between US0.007 billion and US248.98 billion. Conclusion: Diabetes is forecast to create a huge economic burden on national health systems, society, and the economy. A concerted effort is required to prepare for such changes. To gain a more holistic understanding of the future costs of diabetes, it is vital to expand the research in developing countries.